2017
DOI: 10.1159/000478965
|View full text |Cite
|
Sign up to set email alerts
|

Clearance of Selected Plasma Cytokines with Continuous Veno-Venous Hemodialysis Using Ultraflux EMiC2 versus Ultraflux AV1000S

Abstract: Background: High cutoff hemofilters might support the restoration of immune homeostasis in systemic inflammation by depleting inflammatory mediators from the circulation. Methods: Interleukin (IL)-6, IL-8, IL-10, and tumor necrosis factor-alpha depletion was assessed in 30 sepsis patients with acute renal failure using continuous veno-venous hemodialysis with high cutoff versus standard filters (CVVHD-HCO vs. CVVHD-STD) over 48 h. Results: The transfer of IL-6 and IL-8 was significantly higher for CVVHD-HCO, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 30 publications
4
18
0
Order By: Relevance
“…Previous studies explored cytokine changes and cytokine removal by the EMiC2 filter, but none have fully investigated the various mechanisms of cytokine clearance in critically ill patients with sepsis [19][20][21][22]. Despite reported decent removal of IL-6, IL-8, IL-1β, and TNF-α (MW 8.4 to 25 kDa) in-vitro, the effluent clearance rates varied markedly in humans [20,21,37]. Our data show that the majority of cytokines did not achieve high SCs apart from IL-8, IL-4 and MCP-1.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies explored cytokine changes and cytokine removal by the EMiC2 filter, but none have fully investigated the various mechanisms of cytokine clearance in critically ill patients with sepsis [19][20][21][22]. Despite reported decent removal of IL-6, IL-8, IL-1β, and TNF-α (MW 8.4 to 25 kDa) in-vitro, the effluent clearance rates varied markedly in humans [20,21,37]. Our data show that the majority of cytokines did not achieve high SCs apart from IL-8, IL-4 and MCP-1.…”
Section: Discussionmentioning
confidence: 99%
“…Some of our findings are compatible with data in the literature but not all. For instance, a previous study demonstrated higher IL-6 and IL-8 clearance by the EMiC2 filter than the standard membrane, but showed no difference in plasma cytokine decline over time [20]. Another study showed comparable IL-6 clearance between the EMiC2 and high-flux membrane [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations